Resistance and Susceptibility to Filarial Infection with Litomosoides sigmodontis Are Associated with Early Differences in Parasite Development and in Localized Immune Reactions - Babayan, Simon (American Society for Microbiology, 2003)
In order to understand natural resistance to filariasis, we compared Litomosoides sigmodontis primary infection of C57BL/6 mice, which eliminate the worms before patency, and BALB/c mice, in which worms complete their development and produce microfilariae. Our analysis over the first month of infection monitoredmigration of the infective larvae from the lymph nodes to the pleural cavity, where the worms settle. Although immune responses from the mouse strains differed from the outset, the duration of lymphatic migration (4 days) and filarial recovery rates were similar, thus confirming that the proportion of larvae that develop in the host species upon infection is not influenced by host genetic variability. The majority of worms reached the adult stage in both mouse strains; however, worm growth and molting were retarded in resistant C57BL/6 mice. Surprisingly, the only immune responses detected at 60 h postinfection occurred in the susceptible mice and only upon stimulation of cells from lymph nodes draining the inoculation site with infective larva extract: massive production of interleukin-6 (IL-6) and IL-5 (the latter cytokine was previously suspected to have an effect on L. sigmodontis growth). However, between days 10 and 30 postinfection, extraordinarily high levels of type 1 and type 2 cytokines and expansion of pleural leukocyte infiltration were seen in the resistant C57BL/6 mice, explaining the destruction of worms later. Our results suggest that events early in the infection determine susceptibility or resistance to subsequent microfilarial production and a parasite strategy to use specific immune responses to its own benefit.